Perspectives on topicalization : the case of Japanese Wa - Hinds, John; Maynard, Senko K.; Iwasaki, Shōichi (Typological studies in language ;, 1987)
Within the field of Japanese linguistics, few areas have generated as much controversy as the morpheme wa; traditionally described as a marker of old or contrasted information, its function as a discourse marker has also been studied. This work aims to deepen the understanding of wa through careful examination of the particle at both sentence and discourse levels in old Japanese as well as present-day Japanese. Previous studies have concentrated on syntactic analyses of wa. The contributors to this volume challenge the old approach and uncover new properties of wa. The four topics discussed ar.